Bioactive Molecules from Marine Microorganisms - Mazur-Marzec, Hanna; Toruńska-Sitarz, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
For this Special Issue book, ten papers focusing on novel bioactive molecules from different marine microorganisms, including fungi, cyanobacteria, actinobacteria and diatoms, were selected. The isolated biomolecules represent different structures and showed anticancer, antiviral, antifungal, antibacterial, anti-inflammatory and enzyme-inhibiting activities. One of the papers is a review article on microviridins, a class of bioactive cyanobacterial peptides.